DETERMINATION OF COMPANY VALUE IN THE ENERGY AND BASIC MATERIAL SECTOR - Frengki Putra Ramansyah; Rico Nur Ilham (Universitas Efarina, 2025)
This research investigates the determinants of company value within the Energy and Basic Materials sectors listed on the Indonesia Stock Exchange (IDX) from 2021-2023. It examines the impact of Carbon Emission Disclosure (CES), Green Innovation (IH), Environmental, Social, and Governance (ESG), Eco-efficiency (EFI), and Environmental Performance (KL) on Tobin's Q as a measure of company value. The analysis, employing panel data regression with a Fixed Effect Model (FEM), reveals that while ESG, EFI, and KL positively influence company value, CES has a negative impact, and IH shows an insignificant effect. These findings provide insights for companies aiming to enhance their market value by prioritizing environmental and social responsibility.